2011
DOI: 10.3855/jidc.1247
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of the Pandemic H1N1 Influenza global outbreak 2009 among medical students in Karachi, Pakistan

Abstract: Introduction: This study aimed to assess student awareness of the pandemic pdmH1N1, including the students' attitudes and perceptions about treatment, severity of disease and preventive measures. Methodology: A cross-sectional study was conducted among medical students of Dow University of Health Sciences, Karachi. The data were collected through a self-administered questionnaire and results were analyzed using SPSS version 16. Results: A total of 396 medical students participated in this study with a mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 7 publications
1
28
1
Order By: Relevance
“…surveyed medical students of Karachi and observed that they use television and newspaper as the source of information. [11] However, in our study, the most common source from where pharmacy students get knowledge was textbooks and reported to be very confident on such source of knowledge. Second, they get knowledge from the internet but did not feel confident on such sources of information.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…surveyed medical students of Karachi and observed that they use television and newspaper as the source of information. [11] However, in our study, the most common source from where pharmacy students get knowledge was textbooks and reported to be very confident on such source of knowledge. Second, they get knowledge from the internet but did not feel confident on such sources of information.…”
Section: Discussionmentioning
confidence: 68%
“…The knowledge of medical students was reported previously in another study. [11] In countries like Pakistan, mostly female students acquire admission in medical or health sciences, and thus, the current research also accounts majority participants as females (76.7%). As only final year Pharm.D program comprises study population, there was a minor variation in the age of participants.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations